HARMONIZATION OF REGULATIONS ON RECIPIENTS OF GRANTS AND SOCIAL ASSISTANCE BASED ON LOCAL AUTONOMY IN THE CITY OF SURABAYA - Kusumaputra, Ardhiwinda; Retnowati, Endang; Winarno, Ronny (PRANATA HUKUM, 2025)
Regulations concerning grants and social assistance, particularly at the Surabaya City level, still lack legal certainty. The regulations contained in Surabaya Mayor Regulation No. 25 of 2016 and its amendments are inconsistent with higher-level regulations, one of which is Minister of Home Affairs Regulation No. 77 of 2020. In this situation, harmonization of regulations is needed to provide legal certainty that is fair. Using a normative juridical method, with a regulatory and conceptual approach. The findings of this study indicate the need for regulatory harmonization from a philosophical, sociological, and juridical perspective. Grants and social assistance are highly relevant to the state's goal of improving the welfare of its people, so access to them must be based on clear regulations. This will ultimately provide equitable benefits to the community. In addition, harmonization is directed at material regulatory changes. Several aspects of the regulations include the target recipients, use, and duration. Furthermore, it needs to be reconstructed, especially with regard to the duties or authorities of the administrators. One of the findings is the strengthening of the Regional Work Unit in managing Social Assistance.